Structural Characterization and Immune Activity Screening of Polysaccharides With Different Molecular Weights From Astragali Radix - Li, Ke; Cao, Y-x; Jiao, S-m; Du, G-h; Du, Y-g; Qin, X-m (Frontiers in Pharmacology, 2020)
Saccharides are the most abundant substance with the strongest immunological activity in Astragali Radix (AR). However, systematic structure study and immunoactivity screening of polysaccharides with different molecular weights (Mw) in AR have yet to be conducted. In this study, Astragalus polysaccharides (APSs) were divided into three fragments of different Mw values, >2000 kDa (APS-Ⅰ), about 10 kDa (APS-Ⅱ), and about 300 Da (APS-Ⅲ), by using ultrafiltration for the first time. The structural differences of the three products were determined on the basis of monosaccharide composition, FT-IR spectrum, linkage analysis, and nuclear magnetic resonance analysis. Cellular immune activity experiments in vitro and cyclophosphamide immunosuppression animal model experiments in vivo for nonspecific and specific immunoactivity screening were applied to identify the most immunogenic fragment in APSs. Linkage analysis results showed that APS-Ⅰ, APS-Ⅱ, and APS-Ⅲ have different attachment sites of monosaccharide residues. Immune screening experiments indicated that the Mw of the APSs influenced their activity, and APS-Ⅱ had the strongest immunoenhancing activity among the products. This research may serve as a reference for further study on APSs with different structures and immune activities, and as a guidance for the quality control of APSs and the development of new APS products.